Improving Student Learning Outcomes in Islamic Cultural History Learning with the Role Playing Method at MTs S Islamiyah Padanggarugur - Harahap, Kartini (Jurnal Profesi Guru Indonesia, 2025)
This study aims to determine efforts to improve learning achievement of Islamic Cultural History through the Role Playing method in Class VII students of Madrasah Tsanawiyah Swasta Islamiyah Padanggarugur. This study uses action research on Class VII students of Madrasah Tsanawiyah Swasta Islamiyah Padanggarugur. The process of implementing this classroom action research uses two cycles with the Role Playing method. The subjects of the study were 29 students. The data collection method used observation, documentation, and testing methods. The collected data were analyzed using descriptive analysis. The results of the study indicate that the Role Playing method in learning Islamic Cultural History makes it easier for teachers to achieve the desired learning objectives and optimize or complete student learning achievements. The results of the study and discussion can improve learning achievement of Islamic Cultural History on the material of the Development of Science during the Umayyad Dynasty in class VII students of Madrasah Tsanawiyah Swasta Islamiyah Padanggarugur and make it easier for teachers to achieve the desired learning objectives. Based on the results of the research that has been done, it can be concluded that the application of the Role Playing Method in the SKI subject of the material on the development of science during the Umayyad dynasty can improve the learning outcomes of class VII students of the Padanggarugur Private Islamic Junior High School. This can be seen from the increase in the percentage results in each cycle. In the pre-cycle, the percentage of completion was 20.68. The percentage of completion increased in cycle I, which was 75.86%, and in cycle II, the percentage of completion was 93.13%. In cycle II, it was stopped because 100% of students had achieved completion, so the application of the Role Playing Method can be said to be successful in improving the learning outcomes of SKI material on the development of science during the Umayyad dynasty of class VII of the Padanggarugur Private Islamic Junior High School.